2011
DOI: 10.1261/rna.2821711
|View full text |Cite
|
Sign up to set email alerts
|

The role of SmpB and the ribosomal decoding center in licensing tmRNA entry into stalled ribosomes

Abstract: In bacteria, stalled ribosomes are recycled by a hybrid transfer-messenger RNA (tmRNA). Like tRNA, tmRNA is aminoacylated with alanine and is delivered to the ribosome by EF-Tu, where it reacts with the growing polypeptide chain. tmRNA entry into stalled ribosomes poses a challenge to our understanding of ribosome function because it occurs in the absence of a codonanticodon interaction. Instead, tmRNA entry is licensed by the binding of its protein partner, SmpB, to the ribosomal decoding center. We analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 42 publications
8
63
1
Order By: Relevance
“…We found that alanine substitution at this position, or substitution of conserved lysines in the region encompassing residues 131-134, decreased the tagging ability of SmpB. This finding is qualitatively consistent with previous studies (30), although the defects we observed were not as severe. Nonetheless, the SmpB G132D and SmpB K131A/K133A/K134A substitutions demonstrate that this region plays a critical role in SmpB function during trans-translation.…”
Section: Contribution Of the C-terminal Tail And A-site Proximal Resisupporting
confidence: 93%
See 3 more Smart Citations
“…We found that alanine substitution at this position, or substitution of conserved lysines in the region encompassing residues 131-134, decreased the tagging ability of SmpB. This finding is qualitatively consistent with previous studies (30), although the defects we observed were not as severe. Nonetheless, the SmpB G132D and SmpB K131A/K133A/K134A substitutions demonstrate that this region plays a critical role in SmpB function during trans-translation.…”
Section: Contribution Of the C-terminal Tail And A-site Proximal Resisupporting
confidence: 93%
“…Several conserved nucleotides are essential constituents of this region, alterations of which have severe consequences on tmRNA tagging activity. For instance, substitution of the adenine at position 86 (A86) with cytosine in the E. coli tmRNA nearly abolishes all tagging activity (30,40). This particular sub- .…”
Section: Contributions Of the Resume Codon Proximal Portion Of The Tmmentioning
confidence: 95%
See 2 more Smart Citations
“…Within the TLD-SmpB complex, SmpB mimics the anticodon arm of a canonical tRNA [6]. The C-terminal tail of SmpB has been shown to mimic mRNA, and play an essential role in the functioning of ribosome-bound tmRNA [7,8].…”
Section: Introductionmentioning
confidence: 99%